Managing municipal household solid waste towards sustainable environment: a study on households in Section 17, Shah Alam, Selangor / Mohd Faizol Rizal Mohd Rasid - Mohd Rasid, Mohd Faizol Rizal (2015)
Municipal solid waste management is one of the most challenging issues and problems faced by many governments of the developing countries across the world. Improper and poor municipal solid waste management in most developing countries has left a serious and negative impact on the environment. Consequently, it has been identified as one of the main environmental issues in Malaysia. The main objective of this study was to examine the factors that affect municipal household solid waste management in Section 17, Shah Alam and the impact on the environment. This study examined the relationship between (i) households’ lifestyle, (ii) attitude and awareness towards municipal household solid waste management, (iii) the provision of facilities and services provided for municipal household solid waste and the impact on the environment. A total of 379 households in Section 17, Shah Alam, Selangor selected as the sample for this study. A set of questionnaire was distributed to the respondents and analyzed. The results demonstrated significant relationships between households’ lifestyle, attitude and awareness towards municipal household solid waste management, the provision of facilities and services provided for municipal household solid waste and the impact on the environment. The results also revealed that households’ lifestyle was the most significant factor that affects municipal household solid waste management impacting on the environment. Findings from this study would be beneficial to the Shah Alam City Council (SACC) in providing the most effective municipal household solid waste management.